2014
DOI: 10.2214/ajr.12.10475
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Idiopathic Arthritis of the Axial Joints: A Systematic Review of the Diagnostic Accuracy and Predictive Value of Conventional MRI

Abstract: There is fair (grade B) evidence that MRI is an accurate diagnostic method for evaluating early and intermediate changes in the TMJ in JIA and insufficient evidence to indicate MRI is an accurate diagnostic method for detecting JIA in the spinal (grade I) and sacroiliac (grade I) joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
0
38
0
1
Order By: Relevance
“…15 However, for early and intermediate TMJ changes in JIA, there is only level II evidence that MRI is accurate for disease detection, with low observer agreement seen for individual MRI signs. 4 Moreover, there is a radiologic overlap in MRI findings between normal pediatric TMJs and TMJs of mild JIA. In this study, synovial enhancement, a finding typically associated with synovitis in JIA, was seen in more than half the non-arthritic TMJs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 However, for early and intermediate TMJ changes in JIA, there is only level II evidence that MRI is accurate for disease detection, with low observer agreement seen for individual MRI signs. 4 Moreover, there is a radiologic overlap in MRI findings between normal pediatric TMJs and TMJs of mild JIA. In this study, synovial enhancement, a finding typically associated with synovitis in JIA, was seen in more than half the non-arthritic TMJs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Characteristic MRI findings indicating TMJ involvement are synovial hypertrophy, synovitis, and joint effusion. 4,5 Late changes include erosions, subchondral cyst formation, condylar volume loss, and abnormal disc morphology. 4,5 In contrast, MRI findings of the healthy pediatric TMJ are not well reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current literature, MRI is considered the golden standard in detection of early TMJ arthritis in patients with JIA. 29 In contrast, routine MRI is of less clinical value in patients with TMJ arthritis-related signs and symptoms, since only a limited association is shown between orofacial symptoms and TMJ MRI findings. 20,[30][31][32][33] Supporting this, Arabshahi et al 31 found no association between clinical improvements in maximal mouth-opening capacity and resolution of MRI effusion at follow-up after TMJ arthritis treatment with intra-articular steroid injections.…”
Section: Stoustrup and Koosmentioning
confidence: 99%
“…In general, MRI is the method of choice in evaluation of cervical spine arthritis and is most useful in detecting synovitis with hypertrophic, enhanced synovia and pannus formation, joint effusion, erosions, bone marrow edema and possible neural structure compressions [10, 11]. The diagnostic accuracy and predictive value of conventional MRI in JIA patients with axial joint involvement have been poorly investigated [12]. The role of MRI in detecting early changes in cervical spine in JIA was first evaluated in a Turkish study showing higher sensitivity of MRI compared to radiography for detection of erosions in children [13].…”
Section: Introductionmentioning
confidence: 99%